What has the Constitutional Court Given Us? Afriforum v University of the Free State 2018 (4) BCLR 387 (CC) - Mokgadi Margaret Mokgokong; Moses Retselisitsoe Phooko (Obiter, 2019)
The history of South Africa is an unpleasant one. It was a society based on racial segregation with the promotion of Afrikaner culture and the Afrikaans language above all other languages. This can be traced to the architect of apartheid, the Afrikaner National Party, which introduced apartheid. Afrikaans-speaking people, through the Afrikaner National Party, dominated South Africa politically. Their language too, was promoted above all other languages. For example, Afrikaans enjoyed more privileges than other languages in that it was used for drafting laws, as the language of record in the courts and was also the only compulsory subject for learning. The apartheid government, through its racial policies, used the Afrikaans language as a tool to control Black South Africans in almost all spheres of life, including education, which had to be undertaken in Afrikaans. It is therefore no surprise that there were five universities that offered education mainly in Afrikaans. These are Stellenbosch University, University of the Free State, University of Pretoria, Potchefstroom University for Christian Higher Education (now North-West University) and Randse Afrikaanse Universiteit (now University of Johannesburg). The use of the Afrikaans language as an instrument for social control was not sustainable. The new constitutional dispensation ushered in an era wherein respect for fundamental human rights and freedoms is at the top of the South African agenda. The right to further education is constitutionally recognised in section 29(1)(b) of the Constitution of the Republic of South Africa, 1996. Section 29(2) of the Constitution further recognises and embraces the diversity of South African society and provides that “everyone has the right to receive education in the official language or languages of their choice in public education institutions where that education is reasonably practicable” (s 29(b) of the Constitution). The State has an obligation to take reasonable measures on a progressive basis to ensure that further education is available and accessible (s 29(1)(b) of the Constitution). In ensuring “effective access to and implementation” of the right to further education, It is notable that, in its endeavour to make further education available and accessible, the State is required to consider several factors such as language policies. In an effort to facilitate the realisation of the right to further education, the Higher Education Act (101 of 1997) was enacted in order inter alia to “redress past discrimination and ensure representivity and equal access to higher education institutions” (preamble to the Act).In the UFS case (CC), the Constitutional Court applied section 29(1)(b) of the Constitution, which provides for the right to further education and the “right to receive education in the official language or languages of [one’s] choice”. This note centres on this decision and seeks to critically discuss and analyse both the majority and minority decisions of the Constitutional Court. The question presented is whether the Constitutional Court has given the public a solution to the issue surrounding the use of either Afrikaans or English as a language medium of instruction in the higher education sector and what the effect of this has been on the development of other languages. The case note is divided into five sections. The facts of the case, the issues put before the court for consideration and the finding of the court are discussed in part 2. Part 3 contains an analysis of the minority and majority judgments. Part 4 considers whether the court has given us any solutions. Part 5 sets out the authors’ recommendations and their conclusions.